2017
DOI: 10.1088/1361-665x/aa7245
|View full text |Cite
|
Sign up to set email alerts
|

Mixed effect of main electrospinning parameters on the β-phase crystallinity of electrospun PVDF nanofibers

Abstract: Electrospun polyvinylidene fluoride (PVDF) nanofiber has shown its advantages of producing piezoelectric devices. Although the effect of electrospinning parameters on the formation of β crystalline phase has been investigated, their mixed effect has not been fully understood. In this study, two dependent design of experiments were utilized to systematically control the transformation of crystalline phases by three typical electrospinning parameters, i.e. applied voltage, needle tip diameter and feeding flow ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 20 publications
1
30
0
Order By: Relevance
“…In addition, depending on the experimental conditions used, there is an optimized applied voltage, and it differs from one study to another, indicating the absence of a simple proportionality to F(β). Jiyong et al have observed that an increase of the applied voltage from 14 to 20 kV leads to an increase of the Xc value from 48% to 56.3%, corresponding to an increase of F(β) from 70% to 76% [ 80 ]. Nevertheless, further increases up to 24 kV induce both decreases of Xc and F(β), which can be related to the weakened polarization of the PVDF solution during the stretching.…”
Section: Effect Of Electrospinning Parameters On the β Phase And Tmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, depending on the experimental conditions used, there is an optimized applied voltage, and it differs from one study to another, indicating the absence of a simple proportionality to F(β). Jiyong et al have observed that an increase of the applied voltage from 14 to 20 kV leads to an increase of the Xc value from 48% to 56.3%, corresponding to an increase of F(β) from 70% to 76% [ 80 ]. Nevertheless, further increases up to 24 kV induce both decreases of Xc and F(β), which can be related to the weakened polarization of the PVDF solution during the stretching.…”
Section: Effect Of Electrospinning Parameters On the β Phase And Tmentioning
confidence: 99%
“…Moreover, an increase of the flow rate induces also a rapid collection of fibers on a grounded collector and the presence of a solvent, which limits the crystallization process. Thus, Jiyong et al have observed an increase of the crystallinity for a low flow rate and its decrease at a higher flow rate [ 80 ]. However, Ribeiro et al have observed that the flow rate variation has no significant effect on PVDF crystallinity in a range of 0.5 to 4 mL/h [ 88 ].…”
Section: Effect Of Electrospinning Parameters On the β Phase And Tmentioning
confidence: 99%
“…As such, it can be concluded that the observed changes in crystalline structure of the PLA nanofibers after PEPT are indeed not an effect of the performed PEPT but are the results of the electrospinning process. Other research groups have also already observed an effect of the electrospinning process on the crystalline structure of the resultant electrospun nanofibers, which can be tuned by adjusting the used electrospinning parameters …”
Section: Resultsmentioning
confidence: 99%
“…Other research groups have also already observed an effect of the electrospinning process on the crystalline structure of the resultant electrospun nanofibers, which can be tuned by adjusting the used electrospinning parameters. [46,48,51] Considering the results from the cast layers, it can therefore be concluded that the observed changes in thermal stability, T c and crystallinity for the nanofibers are mainly the result of the electrospinning process performed after plasma modification of the PLA solutions and are not caused by the plasma treatment itself.…”
Section: Cast Pla Layersmentioning
confidence: 96%
“…Class 1, for which poly(vinylidene fluoride) (PVDF) is a typical representative, has a relatively high piezoelectric charge constant owing to the spontaneous polarization of the crystalline dipole 6. The crystalline dipole or polar phase such as the β‐phase in PVDF molecular structures can be formed by an electric field or mechanical drawing . However, PVDF‐based sensors and applications usually lose this electromechanical characteristic because of the phase transformation from polar β‐phase to nonpolar α‐ and γ‐phases at elevated temperatures and residual mechanical strain .…”
Section: Introductionmentioning
confidence: 99%